Small Interference RNA Encapsulated in Liposomes: An Effective Strategy for In vitro Inhibition of SARS-CoV-2 Load - Viana Rodrigues, João Pedro; Gonçalves, Vanessa Pinheiro; Lourenço, Francisco Dantas; Martins, Ronaldo Bragança; do Nascimento, Felipe Rocha; Arruda, Eurico; de Figueiredo Nicolete, Larissa Deadame; Nicolete, Roberto (Coronaviruses, 2025)
BackgroundThe pressing need for effective SARS-CoV-2 antiviral medicines has driven research into innovative therapeutic techniques. RNA interference with small interfering RNAs (siRNAs) has shown promise as an antiviral treatment.ObjectiveWe evaluated the effectiveness of lipid-based nanoparticles as a viable delivery platform for siRNA-based approach against SARS-CoV-2 in vitro infection.MethodsLiposomes were fabricated by microfluidics to incorporate SARS-CoV-2-specific siRNAs based on conserved sections of the Spike protein coding sequence. Nanoparticle tracking analysis was used to evaluate the nanoparticles' physicochemical features. Calu-3 and Vero cell lines infected with SARS-CoV-2 were used to test the efficiency of siRNA-loaded liposomes. RT-PCR was used to determine the viral load by quantifying the SARS-CoV-2 genome.ResultsThe results showed that liposomes efficiently decreased viral load in infected cells with good physicochemical features, such as a mean particle size of about 180 nm, zeta potential of +2.5 mV and encapsulation efficiency (53.6%).ConclusionThese findings imply that lipid-based nanoparticles might be a targeted delivery strategy for siRNA-based approaches.
Keywords: viral load inhibition